Impact of board busyness, directors’ education and experience on firm efficiency in selected Asia-Pacific countries - Tan, Khar Mang (2018)
The primary objective of firms is to maximize profit in sustaining the market competitiveness, which is based to the microeconomic theory of firms. To attain the goal of profit maximization, technical efficiency (TE) of firms is significantly important. Based on the concept of technical efficiency, the production of outputs from the inputs relates to managerial factors of firms. To date, previous studies on firm efficiency are dominated by the determinants of firm-specific characteristics and macroeconomic factors. Therefore, past studies overlook the impact of firms’ managerial factors; especially board busyness on firm efficiency. Board busyness is referred to the busyness level of boards of directors (BOD) among firms. Consequently, the study first aims to extend past studies by examining the relationship between board busyness and firm efficiency in the selected developed and developing countries of the Asia-Pacific (AP) region, a leader of world economic growth. Moreover, the extant literature on board busyness has pointed to a lack of clarification on the long-debated impact of board busyness towards firms. To explain the conflicting impact of board busyness, the study next aims to investigate the moderating impact of directors’ education and experience on the relationship between board busyness and firm efficiency in the selected developed and developing AP countries. The analysis of the study comprises two main stages. In the first stage, Data Envelopment Analysis (DEA) method via production approach is adopted to measure the TE scores of firms. The study discovers that the firms in all selected AP countries are not operating at a relatively optimal scale of efficiency, even though these firms have been managerially efficient to exploit their resources fully during 2009 to 2015. Furthermore, the study discovers that the TE level of the firms in selected developed AP countries is significantly higher compared to the firms in selected developing AP countries, on average.In the second stage, Generalized Least Square (GLS) panel regression analysis based on fixed effect method (FEM) is performed to examine the proposed relationships in relates to directors’ education, directors’ experience, board busyness and firm efficiency. Overall, the empirical findings reveal that the board busyness significantly impacts firm efficiency in all selected AP countries. In the case of directors with higher educational level, the board busyness (i.e. based on median number of external directorships) is significantly unfavourable to firm efficiency. However, in the case of directors with greater experience level (i.e. longer board tenure), board busyness (i.e. based on rule of thumb of three external directorships) is significantly favourable to firm efficiency. The findings are parallel to the firms in selected developed AP countries, where board busyness (i.e. based on median number and rule of thumb three external directorships) significantly impacts firm efficiency. In the matter of directors with higher educational level, board busyness (i.e. based on mean number and rule of thumb of three external directorships) is significantly favourable to firm efficiency. Nevertheless, in the matter of directors with greater experience level (i.e. longer board tenure and greater number of past directorships), board busyness (i.e. based on median number and rule of thumb of three external directorships) is significantly unfavourable to firm efficiency. Likewise in selected developing AP countries, the board busyness (i.e. based on mean number of external directorships) significantly impacts; reduces firm efficiency. Yet, the empirical findings fail to show any significant moderating impact of directors’ education and experience towards the board busyness-firm efficiency relationship. Overall, the study contributes to the firm management for the formulation and implementation of new strategies in improving usage of firms’ resources and to become technically efficient in achieving the goal of profit maximization. Moreover, the study contributes to the policy-makers as the inputs to improve current corporate governance policies. Next, the study contributes to potential investors in making informed investment decision. The study also contributes to the academicians and practitioners in providing informative knowledge and gaps filling on existing finance and efficiency literature.